THE DEVELOPMENT OF CHOLERA VACCINE PRODUCTION: A LITERATURE REVIEW - Rahmawaty, Adira (jfpublisher, 2023)
Introduction. Cholera is a diarrheal disease that causes dehydration and rapid death due to infection with bacterium Vibrio cholerae that develops in the colon. Cholera generally develops in countries with poor sanitation, poverty, and unavailability of clean water such as Africa and South Asian. One of the efforts to prevent cholera transmission to tourists who will visit the country can be conducted through vaccines. Method. This research was made to find out the development of cholera vaccine using the literature search method through PubMed, Elsevier, Google Scholar databases, and credible websites. Result and Analysis. From the results of several literature searches, there is a monovalent O1 serogroup vaccine that contains killed whole-cell bacteria such as Ducoral and live-attenuated bacteria, called Vaxchora. Discussion. In addition, there are bivalent vaccines O1 and O139 serogroups that contain whole-cell killed bacteria such as Shanchol, Euvichol, mORC-Vax, and Cholvax.